Growing up to be an outstanding Filipino scientist: Implications for supporting gifted learners - Mingoa, Thelma Rabago (Animo Repository, 2017)
The Philippines is a developing country, in dire need of economic improvement with the help of science and technology. The rights of the gifted and the talented children and youth is mandated in the Philippine Constitution and other legal documents. The government has been putting much effort into programmes for science education. The outstanding Filipino scientist usually obtained his/her elementary, high school, and college education in the Philippines, and most had the opportunity to do graduate and/or postgraduate studies abroad. Success in science-related activities – such as getting good grades in examinations and in the report card, winning in academic contests, winning in science fairs, and qualifying for the Intel International Science and Engineering Fair – are big boosts to the students' resolve to go into science. Science teachers should have a rich stock of teaching techniques and instructional materials, but before the teachers could become adept with laboratory techniques, they should first "feel at home" in the laboratory themselves.